Language and Law The Role of Language and Translation in EU Competition Law (Springer International Publishing, 2018)
The book provides an overview of EU competition law with a focus on the main developments in Italy, Spain, Greece, Poland and Croatia and offers an in-depth analysis of the role of language, translation and multilingualism in its implementation and interpretation. The first part of the book focuses on the main developments in EU competition law in action, which includes legislation, case law and praxis. This part can be divided into two subparts: the private enforcement of EU competition law, and the cooperation among enforcers, i.e. the EU Commission, the national competition authorities and the national courts. Language is of paramount importance in the enforcement of EU competition law, and as such, the second part highlights legal linguistic skills, showcasing the advantages and the challenges of multilingualism, especially in the context of the predominant use of English as the EU drafting and vehicular language. The volume brings together contributions prepared and presented as part of the EU-funded research project "Training Action for Legal Practitioners: Linguistic Skills and Translation in EU Competition Law".